Population dynamics of Trichiurus lepturus (Linnaeus, 1758) off Veraval - Avinash, R.; Desai, A.Y.; Ghosh, Shubhadeep (Indian Journal of Fisheries, 2014)
Population dynamics of the ribbonfish, Trichiurus lepturus, was studied from April 2008 to March 2009 along Veraval coast (lat. N 20°54’912’’ and long. E 70°21’355’’). Ribbonfishes are exploited mostly by trawls throughout the year with peak catch from September to December. The mean length of T. lepturus in trawls was 76.47 cm. The asymptotic length, growth coefficient and age at zero length were 131.25 cm, 0.13 and -0.0777 years, respectively. The growth performance index was 3.35. Recruitment pattern was trimodal with peak during May to July. The length of recruitment was 27 cm. Total, natural and fishing mortalities were 0.44, 0.13 and 0.31. The exploitation rate and ratio of exploitation were 0.30 and 0.105. The annual total stock, biomass and MSY were 1,91,935 t, 1, 55,277 t and 34,161 t, respectively. Yield and yield per recruit at present fishing effort were 23,682.5 t and 65.13 g, indicating the ribbonfish stock along Veraval coast is underexploited. The fishing pressure can be increased by 120% to obtain maximum yield and biomass.